INTERNATIONAL HUMAN RIGHTS LAW - Ciampi, Annalisa; Milas, Max; Ananthavinayagan, Thamil Venthan; Baranowska, Grażyna; Rachovitsa, Adamantia; Theilen, Jens T.; Kahl, Verena; Arévalo-Ramírez, Walter; Rousset-Siri, Andrés (Taylor and Francis, 2024)
This chapter presents the system of international human rights law. It begins by tracing back the evolution of human rights as a separate branch of international law, from the aftermath of the Second World War, through and post the Cold War, up to the 21st century. Based on this historical introduction, the first sub-chapter presents the doctrinal tenets of international human rights law. This sub-chapter illustrates how adjudicative bodies, political entities, and domestic institutions review State behaviour according to human rights standards. In subsequent sub-chapters, the universal and regional human rights systems are introduced. Each of these sub-chapters highlights the history, sources, and institutions underpinning the respective system. These sub-chapters also underline the unique characteristics of each system. While all chapters include critical reflection, the concluding sub-chapter introduces the reader to critical accounts of human rights, broadly understood to encompass approaches which work to uncover the structure of human rights and their connection to other social phenomena such as relations of marginalisation, oppression, and exploitation.
CRIS-Team Scopus Importer:2024-08-12